Citizens and Peace Mediations in Divided Societies: Identifying Zones of Agreement through a Conjoint Survey Experiment. (October 2022) - Loizides, Neophytos; Psaltis, Charis; Morgan-Jones, Edward; Sudulich, Laura; Popp, Raluca; Baykiz, Tekin
How can areas of potential agreement be identified and endorsed by citizens in protracted conflicts? In an effort to answer this question, the article introduces a conjoint experiment across the ethnically and territorially split communities of Cyprus and tests a range of hypotheses about the structure of public opinion with respect to a future settlement. We test hypotheses on security and credible commitments, the legacy of past negotiations, as well as transitional justice mechanisms following United Nations plans to mediate the conflict between Greek and Turkish Cypriots. Contrary to conventional wisdom, we demonstrate that a zone of possible agreement (ZOPA) exists from a public opinion perspective. We specifically explore power-sharing in the context of security, provisions for the internally displaced, federal courts, and territorial readjustments and highlight their relative importance for public opinion interventions across conflict-ridden societies.